Miniaturized Inline Bandpass Filters Based on Triple-Mode Integrated Coaxial-Waveguide Resonators - Sandhu, Muhammad Y.; Afridi, Sharjeel; Lamecki, Adam; Gomez-Garcia, Roberto; Mrozowski, Michal (IEEE access, 2023)
This work presents a design technique to implement miniaturized cross-coupled bandpass filters in inline physical configurations based on triple-mode resonators. Triple-mode resonances are obtained by using integrated coaxial-waveguide cavity resonators. They consist of two coaxial conducting posts placed in the sidewalls of a rectangular waveguide cavity. In the proposed triplet, a transmission zero (TZ) can be positioned at any of the two sides of the passband by simply locating the coaxial posts either on the same wall or on opposite walls of the rectangular waveguide cavity. Coaxial-to-waveguide mode coupling is implemented by means of coupling screws, which adds flexibility in terms of tuning easiness. Three 9.9-GHz proof-of-concept prototypes corresponding to third- and sixth-order integrated coaxial-waveguide bandpass filters are designed at the electromagnetic-simulation level. Furthermore, the triplet with a TZ below the passband is manufactured and characterized to experimentally validate the engineered 3-D RF filter principle and its underlying design theory.